Multifunctional Actions of Ninjinyoeito, a Japanese Kampo Medicine: Accumulated Scientific Evidence Based on Experiments With Cells and Animal Models, and Clinical Studies - Miyano, Kanako; Nonaka, Miki; Uzu, Miaki; Ohshima, Kaori; Uezono, Yasuhito (Frontiers in Nutrition, 2018)
Herbal medicines are currently used for the treatment of several types of diseases and also used for the improvement of Quality of Life (QOL) of patients over the world, in particular, in Asian countries. In Japan, a Japanese herbal medicine namely kampo medicine has been prescribed for the improvement of QOL of patients. Ninjinyoeito (NYT), composed of 12 herbal plants, is one of kampo medicines and used for helping recovery of diseases and improving several symptoms that suffer patients such as anemia, anorexia and fatigue. Recent scientific research approaches to kampo medicines with cells and animal models enable to prove that NYT has multiple functions for improvement of symptoms. Also, clinical studies using NYT support such actions to be widely used for the improvement of symptoms that reduce the QOL of patients.